Constructing a nomogram based on the distribution of thyroid nodules and suspicious lateral cervical lymph nodes in fine-needle aspiration biopsies to predict metastasis in papillary thyroid carcinoma - Liu, Shui-Qing; Feng, Jia-Wei; Yan, Zhan-Tao; Xing, Xiao-Xiao; Jiang, Wen-Yin; Jiang, Yong; Qian, Feng; Xing, Wei (Frontiers in Endocrinology, 2023)
Abstract Purpose: Elevated concentration of thyroglobulin eluent is a risk factor for lateral cervical lymph node metastasis (LLNM) in papillary thyroid cancer (PTC). We aim to develop a practical nomogram based on the distribution of thyroid nodules and suspicious lateral cervical lymph nodes in fine needle aspiration biopsy (LN-FNAB), including cytopathology and suspicious LLN’s thyroglobulin eluent (Tg to predict the possibility of LLNM preoperative in patients with PTC. Methods: The clinical data of PTC patients with fine needle aspiration biopsy (FNA) admitted to the Third Affiliated Hospital of Soochow University from January 2022 to May 2023 were included in this study. 208 cases in 2022 served as the training set ( 70%), and 89 cases in 2023 served as the validation set ( 30%). Clinical characteristics and LN-FNAB were collected to determine the risk factors of LLNM. A preoperative nomogram was developed for predicting LLNM based on the results of univariate and multivariate analysis. Internal calibration, external calibration, and decision curve analysis (DCA) were performed for these models. Results: The multivariate logistic regression analysis showed that maximum thyroid nodules diameter (OR:2.323, 95%CI 1.383-3.904, P=0.001), Tg (OR:1.007, 95%CI 1.005-1.009, P=0.000), Tg divided by serum thyroglobulin, (Tg/sTg) (OR:1.005, 95%CI 1.001-1.008, P=0.009), cytopathology (OR:9.738, 95%CI 3.678-25.783, P=0.000) (all P < 0.05) had significant impact on the LLNM of patients with suspicious lateral cervical lymph nodes (LLNs). The nomogram showed a better predictive value both in training cohorts (AUC: 0.937, 95% CI, 0.895-0.966) and validation cohorts (AUC: 0.957, 95% CI, 0.892-0.989 ). The nomogram also showed excellent internal and external calibration in predicting LLNM. According to DCA, the diagnostic performance of this model was dependent on the following variables: maximum thyroid nodules diameter, Tg, Tg/sTg and cytopathology. Conclusion: Based on the aforementioned risk factors, we believe that it is necessary to establish a personalized LLNM model for patients with PTC. Through this practical nomogram by combining clinical and Tg risk factors, surgeons could accurately predict the possibility of LLNM preoperatively. The nomogram will help surgeons establish personalized treatment plans before surgery.